THE EFFECT OF LIQUIDITY, LEVERAGE, AND GROWTH OPPORTUNITY ON CORPORATE CASH HOLDING - Madelyn Agrata; Henryanto Wijaya (International Journal of Application on Economics and Business, 2026)
This study examines how liquidity, leverage, and growth opportunity influence cash holding in property and real estate companies listed on the Indonesia Stock Exchange (IDX) during 2022–2024. The research uses a quantitative method with secondary data obtained from published financial statements. A purposive sampling method produced 67 companies and 201 firm-year observations. Data were analyzed using multiple linear regression with EViews 12 and Microsoft Excel. The findings show that liquidity and growth opportunity significantly increase cash holding, implying that firms with stronger short-term financial capacity and greater investment prospects prefer to maintain higher cash reserves. Conversely, leverage has a negative and significant effect, indicating that firms with higher debt levels allocate more funds toward repayment rather than holding cash. The results contribute to the understanding of cash holding behavior and may support managerial decisions related to financial planning.